Golexanolone reduces glial activation in the striatum and improves non-motor and some motor alterations in a rat model of Parkinson's disease - Izquierdo-Altarejos, Paula; Arenas, Yaiza M.; Martínez-García, Mar; Vázquez, Lola; Mincheva, Gergana; Doverskog, Magnus; Blackburn, Thomas P.; Bohnen, Nicolaas I.; Llansola, Marta; Felipo, Vicente (Frontiers in Aging Neuroscience, 2024)
BACKGROUND: Parkinson's disease (PD) affects more than 6 million people worldwide. Patients and animal models with Parkinson's disease (PD) symptoms, along with motor impairment, also show cognitive impairment, fatigue, anxiety, and depression. There are no drugs available for PD that alter the progression of the disease. Evidences suggest that increased GABA levels contribute to reduced expression of tyrosine hydroxylase (TH) and behavioural deficits. TH expression may be restored by blocking GABAA receptors. We hypothesized that golexanolone (GR3027), a welltolerated GABAA receptor modulating steroid antagonist (GAMSA), may improve Parkinson symptoms in a rat model of PD.OBJECTIVES: The aims were to assess if golexanolone improves motor and non-motor symptoms in a rat model of PD and to identify some underlying mechanisms.METHODS: We used the unilateral 6-OHDA rat model. Golexanolone treatment started four weeks after surgery. Motor symptoms were assessed by motorater and CatWalk tests. We also analyzed fatigue (treadmill), anhedonia (sucrose preference test), anxiety (open field) and short-term memory (Y maze). Glial activation and key proteins involved in PD pathogenesis were analysed by immunohistochemistry and western blot.RESULTS: Rats with PD showed motor incoordination and impaired locomotor gait, increased fatigue, anxiety, depression, and impaired short-term memory. Golexanolone improved motor incoordination, some aspects of locomotor gait, fatigue, anxiety, depression, and short-term memory. Golexanolone improved microglia and astrocyte activation and TH loss at 5 weeks after surgery and prevented the increase in α-synuclein at 10 weeks.CONCLUSIONS: Golexanolone may be useful to improve motor and non-motor symptoms that affect the patients' quality of life: anxiety, depression, fatigue, motor coordination and locomotor gait, and some cognitive alterations.